Effect of Er,Cr:YSGG Laser Root Conditioning on the Success of Root Coverage with Subepithelial Connective Tissue Graft: A Randomized Clinical Trial with a 6-Month Follow-Up - Banafsheh Poormoradi; Parviz Torkzaban; Leila Gholami; Amirarsalan Hooshyarfard; Maryam Farhadian (Tehran University of Medical Sciences, 2018)
Objectives: Finding predictable approaches for root surface biomodification is an important challenge in the treatment of gingival recession. This study sought to assess the root coverage percentage by subepithelial connective tissue graft (SCTG) following root surface conditioning with erbium, chromium: yttrium scandium gallium garnet (Er,Cr:YSGG) laser. Materials and Methods: In this split-mouth, randomized clinical trial, 30 teeth with Miller's Class I and II gingival recession were treated with SCTG (the Langer and Langer technique) with (case group) or without (control group) root surface conditioning with Er,Cr:YSGG laser (wavelength=2780 nm, power=0.75 W, H mode, repetition rate=20 Hz). Recession depth (RD), recession width (RW), clinical attachment level (CAL), and probing depth (PD) were assessed at the baseline (one week before surgery) and at 2 and 6 months postoperatively. The amount of root coverage was quantified in the two groups. Data were analyzed using Friedman test and Wilcoxon signed-rank test. Results: No significant difference was noted between the case and control groups in any parameter (P>0.05). Significant improvement occurred in all the measured parameters in the two groups after surgery (P<0.05). The mean root coverage at the end of the study period was 87% and 80% in the case and control groups, respectively (P=0.244), and complete root coverage was achieved in 66% and 60% of the samples in the case and control groups, respectively. Conclusions: Root surface conditioning by Er,Cr:YSGG laser improved the mean root coverage and the percentage of complete root coverage. However, these changes were not statistically significant.